Looking After Everyone Right: The Fishing Lake First Nation Approach to Treaty Settlements - Brooks, Tasha; Kayseas, Bob (Journal of Aboriginal Economic Development, 2025)
This case study explores how Fishing Lake First Nation (FLFN) responded to the $101.3 million “Cows and Plows” settlement under Treaty 4 by choosing long-term, Nation-led investment over one-time payouts. Confronted with internal tensions between per capita distribution demands and the need for intergenerational wealth, FLFN created the Waywaynih Kunawapunteeing Trust, a sovereign, legislated financial structure that protects capital, supports per capita payments through authorized loans, and generates sustainable returns to fund community priorities. Through culturally grounded governance, financial education, and strategic compromise, FLFN offers a replicable model for Indigenous Nations who are navigating the complexities of large-scale settlements. This study highlights the practical and political challenges of balancing immediate member benefit with enduring Nation-building, offering key insights for communities managing similar historic claims.